Music for physical rehabilitation (1987-1996): a literature review and analysis - Scappaticci, Cheryl, author; Davis, William B. (William Barron), advisor; Thaut, Michael H., committee member; Metz, Paul Wesley, committee member; Tucker, Alan, committee member (Colorado State University. Libraries, 1998)
A comprehensive literature review and analysis was conducted on the use of music for physical rehabilitation from 1987-1996. An earlier literature review and analysis of music for physical rehabilitation was published by Staum (1988), which covered the literature from 1950 -1986. The purpose of the current study was to provide music therapists with an updated and comprehensive resource to aid them in choosing effective treatment strategies for clients in need of physical rehabilitation. Pertinent music therapy sources, such as the Journal of Music Therapy, and pertinent non-music sources, specifically electronic bibliographic databases such as Medline, were consulted. Relevant sources were discussed in two chapters; Chapter 4 - An Overview of the Use of Music in the Treatment of Physical Rehabilitation, and Chapter 5- Clinical Implications for the Use of Music in Physical Rehabilitation . Tables containing frequency data supplement the discussion of the findings on treatment modalities, research settings, clinical population, musical applications, and literature sources. An overview of the methodology of all experimental and single-subject studies is provided in Table 8.
Keywords: Music therapy; Music -- Physiological effect